Comparative models of American Indian economic development: Capitalist versus cooperative in the United States and Canada. (December 2014) - Rose, Samuel
The purpose of this article is to use a comparative case study method to evaluate the different existing economic development practices of American Indian peoples in the United States and Canada. The basis of comparison is the organizational structure of businesses with the comparison being between capitalist and cooperative forms. The goal is to understand how organizational type (or mode of production) is connected to the production of contemporary culture and social relations. The main conclusion is that, while not equivalent to traditional indigenous economies, cooperative structures are closer than capitalist ones to facilitating and reproducing traditionalist forms of sociality and cultural production.